2014
DOI: 10.1111/cid.12212
|View full text |Cite
|
Sign up to set email alerts
|

Does Timing of Implant Placement Affect Implant Therapy Outcome in the Aesthetic Zone? A Clinical, Radiological, Aesthetic, and Patient‐Based Evaluation

Abstract: The present study suggests that comparable clinical, radiological, and aesthetic results can be achieved with all treatment protocols. Gingival recession, however, seems to occur in the long term irrespective of the technique used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(72 citation statements)
references
References 52 publications
3
68
0
Order By: Relevance
“…The electronic and manual literature search identified a total of 2,518 articles with 2,399 of these citations excluded after titles and abstracts screening. The full‐text of the remaining 119 citations was reviewed, among which 12 articles met the inclusion criteria (Tables and ) . Five studies compared the early placement protocol with the immediate placement protocol, and four studies compared the early placement protocol with the delayed placement protocol .…”
Section: Resultsmentioning
confidence: 99%
“…The electronic and manual literature search identified a total of 2,518 articles with 2,399 of these citations excluded after titles and abstracts screening. The full‐text of the remaining 119 citations was reviewed, among which 12 articles met the inclusion criteria (Tables and ) . Five studies compared the early placement protocol with the immediate placement protocol, and four studies compared the early placement protocol with the delayed placement protocol .…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis reported a survival rate from 93.6-97.5% for immediate and early implant placement and 92.8% for conventionally inserted implants after 1 year (Hartlog et al 2008). Hof et al (2015) evaluated the aesthetic outcomes after immediate, early and delayed implant placement in the anterior maxilla. They excluded all cases in which soft tissue grafting was performed.…”
Section: Timing Of Implant Placementmentioning
confidence: 99%
“…This, in turn, can trigger soft tissue inflammation with additional bone loss and gingival recession. [2][3][4][5][6] It has been reported that gingival margin levels may be affected by the thickness of the gingival tissues, and that a thin tissue biotype may favor apical displacement of the soft tissue margin. 7 Maintaining an adequate width (~2 mm) of keratinized gingiva around dental implants has been reported to be essential for optimal gingival health.…”
Section: Introductonmentioning
confidence: 99%
“…5, 7 However , this has been disputed. [2][3][8][9] One study 6 reported a correlation between the presence of keratinized tissue, plaque levels and the incidence of mucositis, and theorized that sites with minimal keratinized tissue might be prone to a lower incidence of periodontal pocket formation. 3,10 In the anterior maxilla, however, the contribution of thick, keratinized gingiva to implant esthetics has not been disputed.…”
Section: Introductonmentioning
confidence: 99%